PRODUKSI RUANG PUBLIK PEDESAAN SEBAGAI DESTINASI WISATA: STUDI DESTINASI WISATA MUNCAR - Anis Anjarwati; Purnomo, Daru; Hadiwijoyo, Suryo Sakti (Jurnal Sosial Humaniora, 2024)
The public space of Muncar, a craving tourism destination, is experiencing a major transformation gradually. The advantage of a tourist destination is that it has natural beauty that is still preserved and culture, local wisdom is still preserved from generation to generation by the people of Muncar village. Many people use the Muncar rural tourist destination as a public. The Muncar craving area has transformed from an unkempt area to a well-maintained area and  is producing space with the emergence of new buildings and new faces. This research uses descriptive qualitative methodology, Data is collected through observation and in-depth interviews. This study aims to examine the production of public space in the Muncar rural area using Henry Lefebvre's theory of public space production. Apart from that, to maintain the sustainability of Muncar Rural Tourism  as  a public space that anyone can use and to accommodate various human activities, both individually and in groups.